1999
DOI: 10.2307/3870828
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cis-Acting RNA Leader Elements Required for Chloroplast psbD Gene Expression in Chlamydomonas

Abstract: The psbD mRNA of Chlamydomonas reinhardtii is one of the most abundant chloroplast transcripts and encodes the photosystem II reaction center polypeptide D2. This RNA exists in two forms with 5 Ј untranslated regions of 74 and 47 nucleotides. The shorter form, which is associated with polysomes, is likely to result from processing of the larger RNA. Using site-directed mutagenesis and biolistic transformation, we have identified two major RNA stability determinants within the first 12 nucleotides at the 5 Ј en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(85 citation statements)
references
References 8 publications
(12 reference statements)
6
79
0
Order By: Relevance
“…Light/dark regulation of GUS transcript levels in Chlamydomonas chloroplast transformants carrying rbc L 59 end:GUS genes+ Transformants were grown in 12-h light/12-h dark cycles, total RNA was isolated at time points 11 h dark and 1 h light, and processed as described (legend to Fig+ 2; Materials and Methods)+ RNA gel blots were first hybridized to the atpB probe as a control and, after stripping of the membrane, to the GUS probe+ The increase upon illumination seen in abundance of transcripts of the endogenous atpB gene is due to increased transcription of the atpB gene in light and has been reported previously (Salvador et al+, 1993a)+ The membrane was exposed to X-ray film for 4 h for detection of atpB gene transcripts and for 24 h for detection of chimeric rbc L 59 end:GUS gene transcripts+ Numbers above the lanes denote nucleotide replacements in the rbc L 59 UTR sequence as depicted in Figures 1 and 2+ D: dark (also marked by a filled bar); L: light (also marked by an open bar)+ isolated by genomic complementation (Boudreau et al+, 2000)+ Putative cis-acting elements that are potential targets for RNA-stabilizing proteins have been localized in the 59 UTRs of chloroplast gene transcripts (Higgs et al+, 1999;Nickelsen et al+, 1999)+ A number of proteins were found in in vitro assays to bind to the 59 UTRs of Chlamydomonas chloroplast transcripts (Hauser et al+, 1996) and, in spinach, to the 59 UTRs of transcripts of genes that code for subunits of the ATP synthase complex (Hotchkiss & Hollingsworth, 1999)+ Although the identities and functions of these proteins have not been examined, it is possible that some of them are nucleus-encoded factors involved in mRNA stabilization+…”
Section: Discussionmentioning
confidence: 99%
“…Light/dark regulation of GUS transcript levels in Chlamydomonas chloroplast transformants carrying rbc L 59 end:GUS genes+ Transformants were grown in 12-h light/12-h dark cycles, total RNA was isolated at time points 11 h dark and 1 h light, and processed as described (legend to Fig+ 2; Materials and Methods)+ RNA gel blots were first hybridized to the atpB probe as a control and, after stripping of the membrane, to the GUS probe+ The increase upon illumination seen in abundance of transcripts of the endogenous atpB gene is due to increased transcription of the atpB gene in light and has been reported previously (Salvador et al+, 1993a)+ The membrane was exposed to X-ray film for 4 h for detection of atpB gene transcripts and for 24 h for detection of chimeric rbc L 59 end:GUS gene transcripts+ Numbers above the lanes denote nucleotide replacements in the rbc L 59 UTR sequence as depicted in Figures 1 and 2+ D: dark (also marked by a filled bar); L: light (also marked by an open bar)+ isolated by genomic complementation (Boudreau et al+, 2000)+ Putative cis-acting elements that are potential targets for RNA-stabilizing proteins have been localized in the 59 UTRs of chloroplast gene transcripts (Higgs et al+, 1999;Nickelsen et al+, 1999)+ A number of proteins were found in in vitro assays to bind to the 59 UTRs of Chlamydomonas chloroplast transcripts (Hauser et al+, 1996) and, in spinach, to the 59 UTRs of transcripts of genes that code for subunits of the ATP synthase complex (Hotchkiss & Hollingsworth, 1999)+ Although the identities and functions of these proteins have not been examined, it is possible that some of them are nucleus-encoded factors involved in mRNA stabilization+…”
Section: Discussionmentioning
confidence: 99%
“…In vivo labeling of C. reinhardtii with [ 35 S] was performed as described previously (Nickelsen et al, 1999). For the pulse/chase analysis, the medium containing [ 35 S] was replaced after 15 min by nonradioactive medium, and the incubation was prolonged for 60 min.…”
Section: In Vivo Labeling Of C Reinhardtiimentioning
confidence: 99%
“…The same applies to 5¢UTRs of psbD, petD and psbB transcripts in C. reinhardtii, which were shown to contain the target sites for nucleus-encoded factors involved in the gene-specific stabilization of the corresponding mRNAs (Nickelsen et al 1994;Drager et al 1998;Vaistij et al 2000a). For psbD and petD RNAs, site-directed mutagenesis enabled the precise localization of distinct RNA elements mediating RNA stabilization (Higgs et al 1999;Nickelsen et al 1999).…”
Section: Rbps Interacting With 5¢utrsmentioning
confidence: 99%
“…Analysis of the photosynthetic mutant nac2 revealed that the stability of the psbD mRNA depends on a nucleus-encoded tetratricopeptide repeats protein, which is part of a highmolecular-weight complex mediating its function via the psbD 5¢UTR (Boudreau et al 2000). However, a thorough site-directed mutagenesis of the psbD 5¢region after biolistic transformation of chloroplasts from wild-type cells identified several essential cis-acting elements required for either stabilization or translation of the psbD message (Nickelsen et al 1999). Concomitant in vitro RNA binding assays with the mutant psbD 5¢ versions then demonstrated that the deletion of an U-rich element leading to a defect in psbD mRNA translation in vivo resulted in the inability of binding a protein of 40 kDa (RBP40) to the 5¢UTR in vitro.…”
Section: Rbps Interacting With 5¢utrsmentioning
confidence: 99%
See 1 more Smart Citation